2002
DOI: 10.4049/jimmunol.168.1.427
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Nitric Oxide in a Neurotoxicant- Induced Demyelinating Model

Abstract: Demyelination is often associated with acute inflammatory events involving the recruitment-activation of microglia/macrophage, astrocytes, and leukocytes. The ultimate role of inflammatory products in demyelinating disease and in the survival of oligodendrocytes, the myelin forming cells, is unresolved. The current study examines the role of inducible NO synthase (iNOS)-derived NO in a neurotoxicant-induced model of demyelination. NO levels were greatly elevated in the midline corpus callosum during demyelinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 51 publications
7
56
0
1
Order By: Relevance
“…E: Galectin 3 mRNA was gradually upregulated in microglia in the course of demyelination and remyelination, became detectable at the protein level at 5WD (data not shown), and remained upregulated up to 2WR (5WD, 5 weeks of demyelination; 1WR, 1 week of remyelination; 2WR, 2 weeks of remyelination; Tgfb, transforming growth factor beta; Spp1, osteopontin; Iba1, ionized calcium-binding adaptor molecule 1; IB4, isolectin B4; Slpi, antileukoproteinase; Cd11c, integrin alpha-X, a dendritic cell marker; Gal3, galectin-3; calibration bars in our study, both of which have been shown to be indispensable for remyelination to occur (Arnett et al, 2001;Mason et al, 2001). Interestingly, inducible nitric oxide synthase (iNOS) was found to be induced in the cuprizone model in microglia (Arnett et al, 2002;Liñares et al, 2006) and was moderately protective against demyelination (Arnett et al, 2002). Nonetheless, iNOS was not among the genes expressed in our study.…”
Section: Discussionsupporting
confidence: 53%
“…E: Galectin 3 mRNA was gradually upregulated in microglia in the course of demyelination and remyelination, became detectable at the protein level at 5WD (data not shown), and remained upregulated up to 2WR (5WD, 5 weeks of demyelination; 1WR, 1 week of remyelination; 2WR, 2 weeks of remyelination; Tgfb, transforming growth factor beta; Spp1, osteopontin; Iba1, ionized calcium-binding adaptor molecule 1; IB4, isolectin B4; Slpi, antileukoproteinase; Cd11c, integrin alpha-X, a dendritic cell marker; Gal3, galectin-3; calibration bars in our study, both of which have been shown to be indispensable for remyelination to occur (Arnett et al, 2001;Mason et al, 2001). Interestingly, inducible nitric oxide synthase (iNOS) was found to be induced in the cuprizone model in microglia (Arnett et al, 2002;Liñares et al, 2006) and was moderately protective against demyelination (Arnett et al, 2002). Nonetheless, iNOS was not among the genes expressed in our study.…”
Section: Discussionsupporting
confidence: 53%
“…Together, these data indicate that NLRP3 delays demyelination but does not obviate this process, suggesting the existence of other compensatory mechanisms. This is consistent with studies of other inflammatory genes in the cuprizone model (Arnett et al, 2001(Arnett et al, , 2002Mason et al, 2001;Plant et al, 2007). A TUNEL assay was used to assess differences in cell death after 3 weeks of cuprizone-induced demyelination.…”
Section: Demyelination Is Delayed In Cuprizone-treated Nlrp3supporting
confidence: 56%
“…To examine demyelination, paraffin sections were rehydrated through a graded series of alcohol washes and stained with Luxol fast blue-periodic acid/Schiff base (LFB-PAS) (Sigma-Aldrich) as described previously (Arnett et al, 2002). Sections were read by three blinded readers and graded on a scale from 0 (complete myelination) to 3 (complete demyelination).…”
Section: Il-18mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have demonstrated that microglia can either be directly toxic to oligodendrocytes (Nicholas et al, 2003;Li et al, 2005) or can support oligodendrocyte survival (Pang et al, 2000;Nicholas et al, 2001Nicholas et al, , 2002, with the predominant effect being context dependant. Dichotomous effects of microglia also appear to occur in vivo with reports of either deleterious Mana et al, 2006;Pasquini et al, 2007) or protective effects in response to cuprizone-induced demyelination, the latter particularly predominant during the remyelination phase (Arnett et al, 2001(Arnett et al, , 2002(Arnett et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%